The Council of Nicaea and the Import of Dialectic in a Synodal Process - Thomas Kristiatmo (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
Marking the 1700th anniversary of the Council of Nicaea, the author wishes to present a reading of the Council as a theological event through the thoughts of Bernard Lonergan. The objective of the research is to discover how Lonergan’s insights on ways to better grasp the truth can shed light on some novelty and its implications to the reading of the Council. Making use of hermeneutics and descriptive analytics, the author argues that the Council –when read as a theological event– will show a process of dialectic, one of the eight functional specialties proposed by Lonergan. These famous functional specialties reflect the four distinct levels of consciousness in which humans operate. Dialectic, as the fourth functional specialty, is an integral part of being Church today, especially now as we are moving together in a synodal process.